أسس بناء الجهاز الاداري الكفء : قراءة في عهد الامام علي بن ابي طالب لمالك الأشتر - كاطع أ.م.د.امل هندي (مجلة العلوم السياسية, 2011)
أسس بناء الجهاز الاداري الكفء : قراءة في عهد الامام علي بن ابي طالب لمالك الأشتر